A flaw in the design : a novel - Oates, Nathan (Random House, 2023)
"As a creative writing professor in a bucolic Vermont town, Gil's quiet life is indelibly changed when he receives shocking news: His sister, Sharon, and her husband have been killed in a car accident, and their only son, seventeen-year-old Matthew, is coming to live with Gil and his family. It's with apprehension that Gil and his wife, Molly, greet Matthew. Yes, he has just lost both his parents. But they haven't seen him in seven years, and the last time the families were together Matthew lured Gil's young daughter into a terrifying, life-threatening situation. Since that incident Gil has been estranged from his sister and her flashy, vastly wealthy banker husband. And now: Matthew is their charge, living under their roof. The boy seems charming, smart, and urbane, if surprisingly unaffected by his parents' death. Gil hopes that they can put the past behind them, though he's surprised when Matthew signs up for his creative writing class. Then Matthew begins turning in chilling stories about the imagined deaths of Gil's family and his own parents. Bewildered and panicked with fear and rage, Gil ultimately decides he must take matters into his own hands, before life imitates art"--